2013
DOI: 10.1371/journal.pone.0063153
|View full text |Cite
|
Sign up to set email alerts
|

RANKL/RANK/MMP-1 Molecular Triad Contributes to the Metastatic Phenotype of Breast and Prostate Cancer Cells In Vitro

Abstract: The osteolytic nature of bone metastasis results from a tumor-driven increased bone resorption. Bone remodeling is orchestrated by the molecular triad RANK-RANKL-OPG. This process is dysregulated in bone metastases, mostly via induction of RANKL by tumor-derived factors. These factors increase expression of RANKL, which induce osteoclast formation, function, and survival, thereby increasing bone resorption. RANK is unexpectedly expressed by cancer cells, and the activation of RANKL-RANK pathway correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 40 publications
3
60
0
1
Order By: Relevance
“…RANK-RANKL pathway is a key regulator of bone physiology [1, 2], but also a central player in the onset of BM, as RANKL acts as a chemoattractant for RANK-positive tumor cells [20, 21]. Other studies also revealed its role in tumor cell tropism for sites outside bone, such as lung [22].…”
Section: Discussionmentioning
confidence: 99%
“…RANK-RANKL pathway is a key regulator of bone physiology [1, 2], but also a central player in the onset of BM, as RANKL acts as a chemoattractant for RANK-positive tumor cells [20, 21]. Other studies also revealed its role in tumor cell tropism for sites outside bone, such as lung [22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated functional RANK protein expression on the surface of various cancer cell lines, and in vitro experiments suggest that RANKL stimulation will directly induce molecular pathways associated with tumor cell metastasis. Exposure of RANK-expressing human breast, lung, melanoma and prostate cancer cell lines to RANKL in vitro resulted in increased migration and invasion through collagen or fibronectin matrices 41444647484950. The RANKL-dependent effect is correlated with upregulation of several factors involved in migration, angiogenesis and invasion.…”
Section: Direct (Osteoclast-independent) Pro-metastatic Effects Of Ranklmentioning
confidence: 99%
“…This can lead to new prognostic and predictive markers, and to new potential therapeutic molecules specifically targeting the tumor compartment of bone metastases. Dr. Casimiro showed how pre-clinical research with cancer cell lines and animal models is being translated into clinical models, by sharing gene expression signatures of metastases [15], and showed evidence that targeting RANKL-RANK pathway may also affect the tumor compartment of bone metastases [21].…”
Section: Need To Integrate Microenvironment and Metabolomics With Canmentioning
confidence: 99%